Толерантность как условие межэтнического общения детей и студентов - Шалгимбекова, К.С.; Ломиковская, С. (My University, 2016)
The forming of the culture of international communication is considered to be one of the most modern problems of the present days and it’s also the demand and characteristic feature of the modern society. The purpose of the research is to examine the mechanism for the approval of the idea of tolerance in the system of school and university education. The basic method of the research is analytical. The result of the research is presented by the detailed and visual research of this problem that can help the teachers to plan their work while training the tolerance.
Keywords: tolerance; ethnic groups; accordance; culture; breeding